PERSEPSI PENSYARAH DAN PELAJAR TERHADAP PELAKSANAAN PEMBELAJARAN BERASASKAN MASALAH DI POLITEKNIK - Heong, Yee Mei; Ping, Kong Hie; Sidik, Siti Khairiah; Kiong, Tee Tze; Mohamad, Mimi Mohaffyza (Online Journal for TVET Practitioners, 2018)
Problem-based learning (PBM) is a type of self-conceptual learning approaches by facilitate lecturers and students to form a more effective in learning process. The purpose of this study is to ensure the perception of lecturers and students in the implementation of PBM in polytechnics. This is a descriptive study by using a quantitative approach. The total amount of 80 lecturers and 364 students in Civil Engineering, Electrical Engineering, Mechanical and Trade Engineering at Kota Bharu Polytechnic were selected randomly as the sample of the study. A set of questionnaires was used as a research instrument in this study. All data were analyzed by using SPSS software and presented in the form of frequency, percentage and mean score. The findings show that no problems arise in the implementation of PBM when learning process. The lecturers and students have high knowledge perceptions on PBM with mean score of 4.02 and 3.73 respectively. The findings also showed that lecturers and students have a high level of readiness at PBM with mean score of 4.16 and 4.15 respectively. Therefore, it can be concluded that lecturers and students have a positive perception of PMB implementation, therefore PBM should be practice not only at polytechnics but in all institutions of higher learning.